Home range and foraging habitat preference of Scopoli's shearwater Calonectris diomedea during the early chick‐rearing phase in the eastern Mediterranean. Issue 1 (8th October 2018) - Karris, Georgios; Xirouchakis, Stavros; Maina, Irida; Grivas, Kostas; Kavadas, Stefanos
Abstract : Pelagic seabirds that breed colonially are central‐place foragers; their spatial distribution is restricted to marine areas around their colonies during the chick‐rearing period, when attendance and food provision to their chicks has to be intense. In this study we analyzed the foraging trips of 11 Scopoli's shearwater Calonectris diomedea breeders that were tagged with GPS data loggers during 2014 in oligotrophic waters (Ionian Sea, western Greece), and assessed the range and oceanographic parameters of their foraging habitat. Contrary to previous findings suggesting a varying foraging strategy depending on the breeding stage, the tracked shearwaters made short trips, less than 4 days long, in the vicinity of the colony. By applying the Adaptive Kernel method, their 50% and 95% foraging range was estimated at 6871 km 2 and 23 014 km 2 respectively. In addition, generalized additive models showed that sea surface temperature (<25.5°C), minimum distance from the colony (<100 km), fishing pressure index from small scale fisheries (medium values) along with a two‐dimensional soap film smoother for space (easting, northing) were the most significant factors affecting at‐sea distribution of this marine top predator during the early chick‐rearing period (i.e. 99.9% of the final model deviance). Our study will contribute to the revision of the boundaries of the local Special Protection Area (SPA) of Strofades. It will also address the implementation of specific conservation measures for the species at regional and national scale, and the development of a management plan for the protection of the study area.